2013
DOI: 10.1155/2013/101705
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Mediating the Effects ofγ-Tocotrienol When Used in Combination with PPARγAgonists or Antagonists on MCF-7 and MDA-MB-231 Breast Cancer Cells

Abstract: γ-Tocotrienol is a natural vitamin E that displays potent anticancer activity, and previous studies suggest that these effects involve alterations in PPARγ activity. Treatment with 0.5–6 μM  γ-tocotrienol, 0.4–50 μM PPARγ agonists (rosiglitazone or troglitazone), or 0.4–25 μM PPARγ antagonists (GW9662 or T0070907) alone resulted in a dose-responsive inhibition of MCF-7 and MDA-MB-231 breast cancer proliferation. However, combined treatment of 1–4 μM  γ-tocotrienol with PPARγ agonists reversed the growth inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
(61 reference statements)
2
16
0
Order By: Relevance
“…autophagy induction and ER stress-mediated apoptosis Tiwari et al, 2015). Furthermore, tocotrienols have been successfully used as anticancer agents in combination therapies (Abdul Kani et al, 2013;Malaviya and Sylvester, 2013;Rezaei et al, 2014;Sylvester et al, 2011;Tiwari et al, 2015;Tuerdi et al, 2013;Yusof et al, 2015), as agents against cardiovascular diseases (Prasad, 2011) and as radioprotectors in patients undergoing radiotherapy (Kulkarni et al, 2010;Singh et al, 2013).…”
Section: Thcmentioning
confidence: 99%
“…autophagy induction and ER stress-mediated apoptosis Tiwari et al, 2015). Furthermore, tocotrienols have been successfully used as anticancer agents in combination therapies (Abdul Kani et al, 2013;Malaviya and Sylvester, 2013;Rezaei et al, 2014;Sylvester et al, 2011;Tiwari et al, 2015;Tuerdi et al, 2013;Yusof et al, 2015), as agents against cardiovascular diseases (Prasad, 2011) and as radioprotectors in patients undergoing radiotherapy (Kulkarni et al, 2010;Singh et al, 2013).…”
Section: Thcmentioning
confidence: 99%
“…In fact, direct antiproliferative effect of GW9662 has previously been reported in MCF-7, MDA-MB-231 and MDA-MB-468 cells (Sergeant et al, 2004;Malaviya and Sylvester, 2013). A higher concentration of the antagonist (20 μM) was also reported to cause extensive cell death .…”
Section: Discussionmentioning
confidence: 81%
“…Studies have demonstrated the anticancer effects of rosiglitazone and the activation of peroxisome proliferator-activated receptor-γ agonists in several cancers, including hepatocellular carcinoma, breast cancer and colon cancer among others [26,27,28]. Among the 8 identified drugs, there are few articles showing that fosfosal, stachydrine, nizatidine and benzocaine are associated with cancer.…”
Section: Discussionmentioning
confidence: 99%